Eikenella Corrodens, Cause of a Vulvar Abscess in a Diabetic Adult - Nefise Öztoprak; Ülkü Bayar; Güven Çelebi; Mustafa Basaran; Füsun Cömert (Hindawi Limited, 2007)
We report a case of Eikenella corrodens causing vulvar abscess in a diabetic patient. Eikenella corrodens is a slow growing, nonmotile, facultative anaerobic, Gram-negative bacillus which is commensal of the oral cavity, intestinal and genital tracts. The most common clinical sources of this organism are human bite wounds, head and neck infections and respiratory tract infections. In our knowledge, the presented case is the first report of Eikenella corrodens causing vulvar abscess in a diabetic patient.